Stakeholders’ willingness to support a new PCT scheme: “Carbon for Electricity” in the transport sector - Ziyan Yang; Zhenwu Shi; Jie Liu (Cleaner and Responsible Consumption)
Personal Carbon Trading (PCT) schemes are considered in the transportation sector to control carbon emission. However, there is limited evidence on the potential and feasibility of PCT schemes as a new transportation demand-focused tool. Therefore, we designed a “Carbon for Electricity” scheme, aiming to explore how such schemes can help reduce carbon emissions in China. A survey was conducted with 1020 participants from 113 cities in China, focusing on four stakeholder groups: employees and employers of industrial enterprises, residents and property managers of gated communities. The study tested support for two PCT proposals: electric buses for commuting and microcirculation buses for leisure travel. We used ordered logistic regression to identify factors influencing stakeholder willingness and applied a carbon reduction methodology to estimate the policies' potential impact. The study found that about 75% of participants supported the “Carbon for Electricity” scheme and potential carbon emission reductions at 23130.6 kg per month and 6764.4 kg per month, respectively. The scheme effectively reduces carbon emissions by offering flexible options across both transportation and electricity sectors. We recommend integrating PCT schemes that cover both transportation and electricity sectors, with customized proposals and financial incentives, to achieve comprehensive carbon emission reductions and ensure broad stakeholder support. This study is novel in integrating both transportation and electricity in a PCT framework, providing a new approach to demand-side carbon reduction. The findings contribute to designing more effective and inclusive carbon reduction policies.